Analisis Luas Ruangan Berdasarkan Kebutuhan Rak di Ruang Penyimpanan Berkas Rekam Medis Rawat Jalan di Puskesmas Cangkuang - Dindin Solehudin; Sali Setiatin (Jurnal Health Sains, 2021)
Storage racks are needed to maintain the confidentiality of medical records, maintain medical records from physical damage, and make it easier for officers to retrieve medical records and return medical records. In addition, sufficient storage space is also needed so that the shelves needed can be arranged properly and neatly. Based on initial observations, the medical record file storage space at the Cangkuang Health Center is still narrow and insufficient, as evidenced by the large number of medical record files scattered on the floor and difficult access for officers. This study aims to determine the area of medical file storage space based on the need for storage racks. The research method used is a quantitative descriptive method by describing the results of the research as they are and comparing them with the theory which then draws conclusions. The subject in this study is the outpatient medical record file storage room. The object of this research is the outpatient medical record file and the outpatient medical record file storage rack. The results showed that the number of storage racks at the Cangkuang Health Center was 5 units with a storage area of 5.39 m². If currently there are only 5 shelves, Cangkuang Health Center needs to provide 5 more shelves, and expand the storage space to 13.63 m² so that all current medical record files can be neatly arranged in the shelves and make it easier for officers to retrieve and return them. medical record file.